The Vietnam War : A Military History - Wawro, Geoffrey (New York : Basic Books, 2024)
"The Vietnam War cast a shadow over the American psyche from the moment it began. In its time it sparked budget deficits, campus protests, and an erosion of US influence around the world. Long after the last helicopter evacuated Saigon, Americans have continued to battle over whether it was ever a winnable war. Based on thousands of pages of military, diplomatic, and intelligence documents, [this book] offers a definitive account of a war of choice that was doomed from its inception. ... Wawro narrates campaigns where US troops struggled even to find the enemy in the South Vietnamese wilderness, let alone kill sufficient numbers to turn the tide in their favor. Yet the war dragged on, prolonged by presidents and military leaders who feared the political consequences of accepting defeat. In the end, no number of young lives lost or bombs dropped could prevent America's ally, the corrupt South Vietnamese regime, from collapsing the moment US troops retreated"--
Includes bibliographical references and index.
Keywords: Vietnam War, 1961-1975.; United States; Campaigns; Political aspects -- United States; Vietnam -- History -- 1945-1975.; Vietnam -- History, Military -- 20th century; United States -- History, Military -- 20th century; Vietnam -- Relations -- United States; United States -- Relations -- Vietnam; History